Analisis Implementasi Ekualisasi dalam Penerapan Tax Planning Pajak Pertambahan Nilai (PPN) Terutang Pada PT. XYZ - Miyandini, Regita (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
Value Added Tax (VAT) is one of the main sources of state revenue, imposed at each stage of production and distribution. In practice, companies often face challenges in managing payable VAT, especially due to invoice recording errors, which may result in financial and tax reporting discrepancies. One strategy to address this issue is equalization in tax planning. Equalization is performed by comparing profit and loss reports in the Annual Corporate Income Tax Return (SPT PPh Badan) with VAT Periodic Tax Returns (SPT Masa PPN) and other tax reports to ensure accurate reporting and avoid tax corrections and administrative sanctions. This study analyzes the implementation of equalization in VAT tax planning at PT XYZ. Using a descriptive-comparative method with qualitative and quantitative approaches, the findings indicate that inaccuracies in equalization implementation lead to discrepancies between financial data and tax reporting. Additionally, inaccurate VAT reporting results in administrative sanctions and delays in tax refund claims. The main contributing factors include weaknesses in the supervision system and insufficient staff training. Therefore, optimizing the implementation of equalization alongside improved supervision and employee training is essential to enhance corporate tax compliance.